2014
DOI: 10.1016/j.postcomstud.2014.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of foreign direct investment and entry modes of Polish multinational enterprises: A new perspective on internationalization

Abstract: a b s t r a c tThis study uses firm data to examine the locational trends of foreign direct investment projects undertaken by Polish companies. The findings of the study are consistent with the evolutionary models of internationalization. Companies in the early stages of internationalization are motivated by markets and resource seeking, whereas efficiency seeking and strategic asset seeking are significant motivators in the advanced stages of internationalization. However, our results with respect to Polish c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 36 publications
(23 reference statements)
0
8
0
Order By: Relevance
“…Gorbunova (2012), in the research of transition countries, such as the Czech Republic, Hungary, Poland and the Slovak Republic, suggested that FDI distribution among these countries was influenced by the specific market and institutional factors as: the cost of labour, the real exchange rate, the infrastructure, the inflow of private capital, the business registration costs, the inflation rate, the diffusion of internet users and the rigidity of employment laws. Kowalewski (2014) in the study using firm data examined the locational trends of foreign direct investment projects undertaken by the Polish companies and proved the consistence with the evolutionary models of internationalization. Companies in the early stages of internationalization are markets and resource seeking, whereas efficiency seeking and strategic asset seeking are the companies in the advanced stages of internationalization.…”
Section: Literature Reviewmentioning
confidence: 80%
“…Gorbunova (2012), in the research of transition countries, such as the Czech Republic, Hungary, Poland and the Slovak Republic, suggested that FDI distribution among these countries was influenced by the specific market and institutional factors as: the cost of labour, the real exchange rate, the infrastructure, the inflow of private capital, the business registration costs, the inflation rate, the diffusion of internet users and the rigidity of employment laws. Kowalewski (2014) in the study using firm data examined the locational trends of foreign direct investment projects undertaken by the Polish companies and proved the consistence with the evolutionary models of internationalization. Companies in the early stages of internationalization are markets and resource seeking, whereas efficiency seeking and strategic asset seeking are the companies in the advanced stages of internationalization.…”
Section: Literature Reviewmentioning
confidence: 80%
“…A survey conducted among Polish international companies indicated that their FdI -just as the investments of firms from developed countries -were motivated, among others, by the willingness to use the resources developed on the home market (Jaworek, 2008;Jaworek, 2013;Gorynia et. al., 2015), and much less frequently by the need to find resources on a foreign market (Jaworek, 2008;Jaworek, 2013;Kowalewski and Radło, 2014). The outcomes of a research conducted by Gorynia et al (2015) also indicated that the said resources were mainly connected with entrepreneurial and managerial skills, and the ability to develop and leverage business networks abroad.…”
Section: Internal Development Determinantsmentioning
confidence: 99%
“…The available literature on the subject includes numerous research papers which discuss the question of foreign establishment mode choice (e.g. Hennart & Park, 1993;Brouthers & Brouthers, 2000;Datta, Herrmann, & Rasheed, 2002;Werner, 2002;Larimo, 2003;Shimizu, Hitt, Vaidyanath, & Pisano, 2004;Brouthers & Hennart, 2007;Gorynia, 2007;Slangen & Hennart, 2007;Slangen & Hennart, 2008;Demirbag, Tatoglu, & Glaister, 2008;Demirbag, Tatoglu, & Glaister, 2009;Arslan & Larimo, 2011;Slangen, 2011;Jiménez-Burillo & Jiménez-Moreno, 2013;Kowalewski & Radło, 2014;Gorynia, Nowak, Trąpczyński, & Wolniak, 2015a;Gorynia, Nowak, Trąpczyński, & Wolniak, 2015b;Shen & Puig, 2017;Holtbrügge & Berningn, 2018). They focus primarily on identifying the determinants of the choice between alternative capital investment options available on the host market.…”
Section: Literature Review Fdi Establishment Mode Strategymentioning
confidence: 99%